Comparison of colorectal cancer screening between people with and without disability: a nationwide matched cohort study - Chun-Ming Liao; Wen-Hao Huang; Pei-Tseng Kung; Li-Ting Chiu; Wen-Chen Tsai (BMC, 2021)
Abstract Background The World Health Organization has recognized that people with disability are among the most marginalized in the world. This study's objective was to investigate the differences in the probability of colorectal cancer (CRC) screening with faecal immunochemical testing (FIT) between people with disability and without disability in Taiwan. Methods The study participants included people with and without disability from the Disability Registration Database (2012) and the National Health Insurance Research Database (2009-2012). The study included 50- to 69-year-olds with and without disability who were screened from 2011 to 2012 and were alive in 2012. There were 16 categories of disability. After propensity score matching (PSM) between the two groups, conditional logistic regression analysis with control variables was used to investigate the odds ratio (OR) that people with or without disability would undergo CRC screening. Results The percentage of people with disability receiving CRC screening was 21.84%, and the highest rate of those receiving CRC screening (38.72%) was found in people with intractable epilepsy, whose OR was 1.47 times that of people with moving functional limitation (95% confidence interval (CI) = 1.17-1.85). The results showed that the probability of CRC screening in people with disability was lower than that in people without disability (OR = 0.88, 95%CI = 0.87-0.89). The probability of receiving CRC screening differed between people with different categories of disability. Conclusions Although the probability of CRC screening in the four categories of disability was higher than that in the general population, overall, people with disability were less likely than people without disability to undergo CRC screening. Health inequalities still exist under National Health Insurance in Taiwan.